Therapeutic effect of laparoscopic salpingotomy vs. salpingectomy on patients with ectopic pregnancy: A systematic review and meta-analysis - Wenjing, Lin; Haibo, Li (Frontiers in Surgery, 2022)
Background and aim: Laparoscopic treatment of ectopic pregnancy mainly includes laparoscopic salpingotomy and salpingectomy. We aimed to assess the therapeutic effect of laparoscopic salpingotomy and salpingectomy on patients with tubal pregnancy. Methods: From January 2000 through June 2022, the Cochrane Library, Medline, PubMed, Web of Science, EMBASE, and the Chinese Biomedicine Database were searched for studies that compared the therapeutic effect of laparoscopic salpingotomy versus salpingectomy in the treatment of tubal pregnancy. Results: Twenty-four randomized clinical trials (RCTs) studies were incorporated into this analysis. No statistical differences were found between the two groups in terms of operation duration and postoperative hospitalize length, but the volume of intraoperative blood loss in patients with laparoscopic salpingotomy was less than that in salpingectomy. Importantly, the natural intrauterine pregnancy rate after laparoscopic salpingotomy was significantly higher than those who underwent salpingectomy. In addition, laparoscopic salpingotomy can better protect the ovarian reserve function and endocrine function and provide favorable conditions for the second pregnancy. Conclusion: Patients with ectopic tubal pregnancy should give priority to laparoscopic salpingotomy for embryo extraction.